EGFR p.V774M/p.L833V compound mutations in lung adenocarcinoma responded well to almonertinib: a case report - Pan, Hai; Zhang, Linlin; Meng, Fanlu; Guan, Shasha; Zhong, Diansheng (Frontiers in Oncology, 2023)
Background There are about 10-15% of uncommon EGFR mutations found in NSCLC patients, and their sensitivity to EGFR TKIs still lack sufficient clinical evidence, especially for rare compound mutations. Almonertinib is the third generation of EGFR-TKI that has demonstrated excellent efficacy in classical mutations, however, effects in rare mutations have also been rarely reported. Case presentation In this case report, we present a patient with advanced lung adenocarcinoma with a rare EGFR p.V774M/p.L833V compound mutations, who achieved long-lasting and stable disease control after first-line Almonertinib targeted therapy. This case report could provide more information for therapeutic strategy selecting of NSCLC patients harboring rare EGFR mutations. Conclusion We report for the first time the long-lasting and stable disease control with Almonertinib for EGFR p.V774M/p.L833V compound mutations treatment, hoping to provide more clinical case references for the treatment of rare compound mutations.